Continuum Models and Discrete Systems 2004
DOI: 10.1007/978-1-4020-2316-3_60
|View full text |Cite
|
Sign up to set email alerts
|

The Effective Properties of Macroscopically Inhomogeneous Ferromagnetic Composites

Abstract:  Review of theoretical methods for description of thermoelectrical properties of two-phase macroscopically inhomogeneous media is given. Description by means of a hierarchical model of percolation structure is given, allowing a description on a qualitative and quantitative level of the basic regularities of effective thermoelectric coefficient close to flow threshold. А.А. Snarskii I.V. Bezsudnov А.А. Snarskii, I.V. Bezsudnov Thermoelectric properties of macroscopically inhomogeneous composites

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Partial crystallization of the glasses systematically results in decreases in the α values, which can be attributed to the higher Seebeck coefficients of the precipitated crystalline phases. In addition, effective medium theory applied to the Seebeck coefficient demonstrated that above the percolation threshold of the most conductive phase (which is likely achieved in the present samples), the α values of two-phase materials tend rapidly to that of the most conducting phase. , Assuming that this applies in the present case, rough estimates of the Seebeck coefficients of the crystallites for each glass ceramic can be inferred. The Cu 20 As 35 Te 45 and Cu 15 As 30 Te 55 glass ceramics that stabilize the α-As 2 Te 3 and β-As 2 Te 3 crystalline phases, respectively, exhibit α values of 70 and 80 μV·K –1 at 300 K. These results are in fair agreement with the average values of 100 and 150 μV·K –1 measured on pure polycrystalline samples.…”
Section: Results and Discussionmentioning
confidence: 71%
“…Partial crystallization of the glasses systematically results in decreases in the α values, which can be attributed to the higher Seebeck coefficients of the precipitated crystalline phases. In addition, effective medium theory applied to the Seebeck coefficient demonstrated that above the percolation threshold of the most conductive phase (which is likely achieved in the present samples), the α values of two-phase materials tend rapidly to that of the most conducting phase. , Assuming that this applies in the present case, rough estimates of the Seebeck coefficients of the crystallites for each glass ceramic can be inferred. The Cu 20 As 35 Te 45 and Cu 15 As 30 Te 55 glass ceramics that stabilize the α-As 2 Te 3 and β-As 2 Te 3 crystalline phases, respectively, exhibit α values of 70 and 80 μV·K –1 at 300 K. These results are in fair agreement with the average values of 100 and 150 μV·K –1 measured on pure polycrystalline samples.…”
Section: Results and Discussionmentioning
confidence: 71%